Impact of 1/f noise on cosmological parameter constraints for SKA intensity mapping. Issue 3 (26th November 2019) - Chen, T; Battye, R A; Costa, A A; Dickinson, C; Harper, S E
ABSTRACT: We investigate the impact of 1/ f noise on cosmology for an intensity mapping survey with SKA1-MID Band 1 and Band 2. We use a Fisher matrix approach to forecast constraints on cosmological parameters under the influence of 1/ f noise, adopting a semi-empirical model from an earlier work, which results from the residual 1/ f noise spectrum after applying a component separation algorithm to remove smooth spectral components. Without 1/ f noise, the projected constraints are 4 per cent on w 0, 1 per cent on h, 2 per cent on b H i using Band 1+ Planck, and 3 per cent on w 0, 0.5 per cent on h, 2 per cent on b H i using Band 2+ Planck . A representative baseline 1/ f noise degrades these constraints by a factor of ∼1.5 for Band 1+ Planck, and ∼1.2 for Band 2+ Planck . On the power spectrum measurement, higher redshift and smaller scales are more affected by 1/ f noise, with minimal contamination comes from z ≲ 1 and ℓ ≲ 100. Subject to the specific scan strategy of the adopted 1/ f noise model, one prefers a correlation in frequency with minimized spectral slope, a low knee frequency, and a large telescope slew speed in order to reduce its impact.